P-127: Fast Liquid Crystal Light Shutter - Hegde, Gurumurthy; Komitov, Lachezar; Hee Lee, Seung (Blackwell Publishing Ltd, 2011)
A sub-millisecond liquid crystal light shutter driven by a fringe electric field is presented. In order to reduce the fall time of the shutter a polymer network is created in the liquid crystal bulk. Both rise and fall times of this device are found to be in the microsecond region (100-200s).